Polarization-Insensitive Remote Electro-Optic Modulation for Distributed Antenna System Using a Novel Polarization Scrambling Method - Xinwu Yang; Jiaxin Fan; Fucai Zhu (IEEE Photonics Journal)
This study investigates and experimentally demonstrates a novel polarization scrambling method to solve the polarization dependence of remote electro-optic modulation in the fiber-based distributed antenna system. Theoretically, if the polarization state of a monochromatic light is scrambled at a particular depth, the direct current component of the photocurrent would be independent of the polarization perturbation from the fiber link. A proof of concept experiment is performed in which a 500-MHz simulated polarization perturbation from the fiber is successfully suppressed by more than 40 dB. We then apply the proposed scrambling method to a 5-km remote electro-optic modulation fiber link and significantly reduce polarization-dependent intensity fluctuation from 42 to 0.6 dB. Furthermore, we evaluate the proposed scrambling method for remote photonic radio-frequency (RF) mixing, where the fluctuation of the converted signal is stabilized within 0.9 dB.